Determinants of Employed Women's Attitude towards Childbearing - Farnosh Davoudi; Neda Soleimanvandy Azar; Habibeh Ezoji; Khadijeh Ezoji (Mashhad University of Medical Sciences, 2020)
Background & aim: Iranian policymakers have recently shifted away from a birth control towards a pro-fertility policies. In this regard, it is indispensable to recognize the determinants of childbearing willingness to evaluate the influence of these policies on certain target groups. With this background in mind, the present study aimed to find determinants of childbearing willingness in employed women. Methods: In this cross-sectional study, 140 married females, holding non-professional job positions in Iran University of Medical Sciences (IUMS), Tehran, Iran, completed a self-administered questionnaire about demographic characteristics, actual and ideal number of children, own and spouse's willingness to have another child, in addition to perceived incentives and barriers of childbearing. Chi-square test and logistic regression analysis were applied for data analysis. Results: The mean age of participants was reported as 39.48±6.915. The actual and ideal number of participants' children were obtained at 1.32±0.77 and 2.3±1.06, respectively (P-value<0.001). 50 (35.7%) of all respondents were willing to bear a child, including 37(74%) of cases who had at least one child at the time of study and 13 (26%) of those with no children (P=0.016). "The pleasure of having a baby" was their strongest explanation for childbearing desire, while "challenges of raising children" was regarded as the strongest obstacle in the group of participants who were reluctant to have children. On the other hand, in the group of cases who were willing to have a (another) child, "flexible work hours" and " job security during and after maternity leave" were the most important suggested interventions to raise children. Conclusion: "The pleasure of having a baby" and "challenges of raising children" were the most important incentive and obstacle for childbearing, respectively.